Different Root Anatomical Changes in Salt-tolerant and Salt-sensitive Foxtail Millet Genotypes - Nike Karjunita; Nurul Khumaida; Sintho Wahyuning Ardie (AGRIVITA, Journal of Agricultural Science, 2019)
Foxtail millet is relatively tolerant to salinity stress and thus can be grown in salinity affected areas. This study was conducted to identify anatomical changes in the roots of foxtail millet genotypes with different tolerance level to salt stress. Four foxtail millet genotypes, namely ICERI-5 and ICERI-6 (salt tolerant) and ICERI-4 and ICERI-10 (salt sensitive), were grown hydroponically for 1 week prior to 60 and 120 mM salt stress treatments. Root anatomical changes were observed on the fifth day after treatments. The results showed that salt stress significantly induced some anatomical changes in the roots of foxtail millet, i.e. increased epidermis and cortex thickness, increased root diameter, and increased the number of root hairs. The increase in epidermis thickness, root diameter and the number of root hairs due to the salt application were more pronounced in the sensitive genotypes. Number of protoxylem in the tolerant genotypes were significantly increased due to salt stress, however salinity significantly decreased the number of protoxylem in the sensitive genotypes. The different anatomical changes under salt stress between the tolerant- and sensitive genotypes indicated that some anatomical attributes of the roots might determine the salt tolerance level of foxtail millet.